A Review on Perovskite as a Catalyst - Osazuwa, Osarieme U.; Cheng, C. K. (Universiti Malaysia Pahang, 2016)
Majority of catalysts used in the in industry today are mixture of metal oxides. Preparation techniques of mixed metal oxides able to perform complex functions are of growing interest in the field of heterogeneous catalysis today. Carrying out a wide range of catalytic reactions requires catalyst with poly-functional attributes; good solid state, surface and morphological properties. Extensive background knowledge in solid-state kinetics is required in the field of heterogeneous catalysis so as to design catalyst in the engineering field. Among the mixed metal oxides, perovskite-type oxides remain prominent. The perovskite oxides have the general formula ABO3. The diversity of properties that these compounds exhibited is derived from the fact that around 90% of the metallic natural elements of the Periodic Table are known to be stable in aperovskite-type oxide structure. An ideal perovskite structure must adhere to the tolerance factor limits which have been investigated using a case study of the cobalt metal in the B- site in the paper. The tolerance factor has been calculated for the rare earth metal series and alkaline earth metal series with lanthanum, cerium, neodymium, samarium, and calcium all forming stable perovskites.